Effects of maca (Lepidium meyenii) on nutrient digestibility and major nutrient transporters in rats fed a high-fat diet - Şahin, Nurhan; Orhan, Cemal; Gencoglu, Hasan; Er, Besir; Ozercan, Ibrahim H.; Komorowski, James R.; Şahin, Kazım (Wiley, 2021)
Scope: This study was carried out to investigate the efficacy of a new combination of root extracts of the Lepidium meyenii (maca) plant, known for its nutritional and energizing features as well as its antioxidant properties, on nutrient digestibility and nutrient transporters expression. Methods and results: A total of 28 Sprague-Dawley rats (8-week-old) were divided into four groups: (i) control, (ii) Lepidium m., (iii) high-fat diet (HFD), and (iv) HFD+Lepidium m. Maca was given to the rats as a powdered combination of the plant roots with a daily dose of 40 mg per kg BW. Maca administration significantly increased the digestibility of dry matter (DM), organic matter (OM), crude protein (CP), and ether extract (EE), and some nutrient transporter (Pept1/2, Fatp1, Glut1/2, and Sglt1)-expressions compared with non-treated control and HFD groups in the jejunum and ileum tissues (p < .0001). Conclusions: Maca supplementation improved the digestibility of nutrients and expressions of nutrient transporters in the small intestine of the rats. These results indicate the positive communication between maca consumption and nutrient absorption in the small intestines of the animals.
Keywords: digestibility; high-fat diet; maca; nutrient transporters; rat